The Mediating Role of Spiral of Silence in the Effect of Nomophobia on Social Withdrawal - Ayhan Bayram; Ece Zeybek Yilmaz (Addicta: The Turkish Journal on Addictions)
There is limited research in the literature that examines the relationships between the spiral of silence, nomophobia, and social withdrawal among university students. The objective of this research is to explore the mediating role of the spiral of silence/nomophobia/social withdrawal in the influence of nomophobia/ social withdrawal/spiral of silence on social withdrawal/spiral of silence/nomophobia among university students. A survey consisting of three distinct scales was administered to assess levels of spiral of silence, nomophobia, and social withdrawal. Participants were requested to respond to three demographic questions, seven questions related to the spiral of silence construct, twenty questions pertaining to nomophobia, and twenty-two questions regarding social withdrawal. The data collected from a sample of 512 university students through convenience sampling and face-to-face survey techniques were analyzed using statistical software packages such as SPSS Process and Amos. Exploratory factor analysis was conducted to determine the factor structure of the scales. Confirmatory factor analysis was also conducted to confirm whether the research model was consistent and the result was determined to be appropriate. The findings of the study were evaluated at the 95% confidence interval and .05 significance level. The findings of this investigation reveal a statistically significant relationship between the spiral of silence, nomophobia, and social withdrawal variables. This study has been deduced that among university students, the spiral of silence exerts a partial mediating effect on the relationship between nomophobia and social withdrawal (p = .00 < .05).